Communal Lands and Social Revolt: Peru and Bolivia in the 18th century - O'Phelan Godoy, Scarlett (1983)
It is striking that the phenomenon of "land grabs", which has been observed so frequently in indigenous communities during the 19th and 20th centuries, was practically absent from the historical scene in the 18th century.